Innovation for Engineers Developing Creative and Entrepreneurial Success - Mehregany, Mehran (Springer International Publishing, 2018)
Teaches concepts and practices for driving creativity, innovation, entrepreneurship and intrapreneurship; Discusses personal considerations for success and happiness over one's course of career; Describes the power of observation and imagination-the OR Mindset-for in driving innovation; Presents a methodology for innovation opportunity identification, qualification and financing. This book teaches readers the fundamentals of innovation and reduces them to practice in the context of entrepreneurship and intrapreneurship. It is a new, fresh look at learning and practicing innovation at the individual level, based on scientific knowledge and in the context of the 21st Century. Th`e first chapter introduces the topic and describes the author's perspective. Next, an overview of the 21st Century landscape and innovation is presented, as well as a discussion of positioning oneself to stay relevant and fulfilled during the course of one's career. The third chapter teaches how to think creatively by learning the basics of creative thinking processes. The next chapter builds on creative thinking and describes innovation methods, including design, lateral, and systems thinking, and blue ocean strategies. Examples of organizations with a long history of innovation are presented, followed by ideas on measuring and tracking the innovativeness of organizations. The fifth chapter brings the concepts together to teach about launching an innovation project, particularly in the context of startups. The conclusion summarizes the takeaways. This book is written for engineering students and professionals, but can also be used by those in other disciplines by adapting the engineering analogies.